Liposomes as amphiphilic carriers: encapsulation and stability aspects - Sumaira Naeem; Lik, Voon Kiew; Lip, Yong Chung; Muhammad Aqeel Ashraf; Misni Misran (Universiti Kebangsaan Malaysia, 2016)
The aimed of the present study was to evaluate the liposomal formulation regarding its hydrophobicity. The evaluation studies were done based on the amphiphilic nature of the phospholipid liposomes. This paper highlights the importance of such type of lipid based carriers by encapsulation hydrophobic and hydrophilic drug models. Crystal violet and Nile red were used to represent hydrophilic and hydrophobic moieties before moving to pharmaceutical implications. The formulated liposomes were compared for their hydrophobicity using percent encapsulation efficiencies. The purpose of this formulation was to mimic the red blood cells. The average particle size of 120±25.1 and zeta potential of -10.2±1.4 were in good agreement with reported characteristics of the red blood cells. Per cent encapsulation efficiency for crystal violet was more obvious with a value of 68.1 as compared to 36.5% for Nile red. The prepared liposomes were quite stable for a period of one month. Our findings reflect the fate of our system more suitable for hydrophilic drugs under the given set of formulation parameters.